Power to Coalescence: Traditional to Contemporary / Fatima Zahra - Zahra, Fatima (Faculty of Art and Design, 2021)
Painting ignites in me a passion for exploring the world and the intricacies within it. Whether painting a vast landscape, still life, life drawing or exploring some details of life, emotions, and eras, I am taken by the whole process of thinking a subject matter or theme and deciding how to portray it. Different mediums allow me to express different ideas. Using colors, textures and perspectives, I seek to compose interesting compositions and give recognition to the functions and beauty of the things and emotions generally taken for granted. When my paintings stir emotions and attachment for others, the passion I have invested yields an added realm of fulfilment. I hope my paintings provide pleasure for the souls as well as the eyes of viewers.